1997
DOI: 10.2307/2446026
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyanidin reductase activity and accumulation of proanthocyanidins in developing legume tissues

Abstract: Proanthocyanidin (PA) and anthocyanin accumulation and location in developing leaves, flowers, and seeds of the legumes Medicago sativa, Lotus japonicus, Lotus uliginosus, Hedysarum sulfurescens, and Robinia pseudacacia were investigated by quantitative measurements and by histological analysis after staining with 1% vanillin/HCl, butanol/HCl, or 50% HC1. M. sativa leaves and flowers, L. japonicus leaves, and R. pseudacacia flowers do not contain PAs, but seeds of all investigated species contain PAs. Anthocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 35 publications
2
42
1
1
Order By: Relevance
“…This pattern of pigment deposition is similar to that observed by Skadhauge et al (1997) in immature seed coats of alfalfa stained with vanillin. Vanillin staining revealed a strong reduction of PA deposition in the vacuoles of tt12 endothelial cells.…”
Section: Pa Deposition In Vacuoles Of the Endothelium Is Disturbed Insupporting
confidence: 85%
“…This pattern of pigment deposition is similar to that observed by Skadhauge et al (1997) in immature seed coats of alfalfa stained with vanillin. Vanillin staining revealed a strong reduction of PA deposition in the vacuoles of tt12 endothelial cells.…”
Section: Pa Deposition In Vacuoles Of the Endothelium Is Disturbed Insupporting
confidence: 85%
“…The first committed step to PA biosynthesis, and the only one to be enzymically characterized, is catalyzed by the enzyme leucoanthocyanidin reductase (LAR). Reactions catalyzing the conversion of (ϩ)-3,4-cis-leucocyanidin to (ϩ)- gumes (Stafford and Lester, 1984;Tanner and Kristiansen, 1993;Singh et al, 1997;Skadhauge et al, 1997). PA is thought to be synthesized by sequential addition of an intermediate derived from a flavan-3,4-diol (e.g.…”
mentioning
confidence: 99%
“…Relationships between traits were calculated using the Correlation Coefficient module in Microsoft Excel Data Analysis ToolPak. Histochemical staining of PA by butanol:HCl hydrolysis was evaluated by light microscopy according to Skadhauge et al (1997). Two PA-accumulating tan1 and tan2 mutants were selected for analysis from a Tn/T-DNA insertion population of L. c. var.…”
Section: Thirty-twomentioning
confidence: 99%
“…Flowers and seed coats of L. c. var. japonicus ecotype Gifu B129 have been shown to produce moderate to high levels of PA (Skadhauge et al 1997), but polymer size and flavonoid composition have not been reported for this species. Stem anthocyanin levels have been correlated with habitat latitude for 66 wild-grown accessions of L. c. var.…”
mentioning
confidence: 94%
See 1 more Smart Citation